Fry Is Required for Mammary Gland Development During Pregnant Periods and Affects the Morphology and Growth of Breast Cancer Cells - Liu, Yan; Chen, Xushen; Gong, Zhihong; Zhang, Hao; Fei, Fan; Tang, Xiaojiang; Wang, Jie; Xu, Peilin; Zarbl, Helmut; Ren, Xuefeng (Frontiers in Oncology, 2019)
The Fry gene, located on chromosome 13, is an evolutionarily conserved large protein from yeast to human. Our previous study genetically linked the Fry gene with differential susceptibility to mammary carcinogenesis, but whether Fry affects mammary gland development and function, as well as the growth of breast cancer cells, is largely unknown. To define the consequences of Fry loss in the mammary glands, we have generated mice conditionally deficient of the Fry gene in the mammary glands using the Cre-loxP recombination system. We examined multiple phenotypes with male and female homozygous Fry conditional knockout mice (Mfry) and control mice (WT), including body weight, preliminary observations (health and neurological flexes), open field locomotion, sensory abilities, auditory threshold, and glucose metabolism. The loss of Fry in the mammary glands didn’t cause a significant difference in these genotypes between Mfry and WT mice. However, our data showed that Fry was required during pregnancy, while it was functionally dispensable in virgin mammary gland development. Loss of Fry led to more lateral buds, and the lobuloalveoli were smaller and showed undistended morphology in mammary glands during late pregnancy. In vitro experiment, ectopic expression of FRY could alter the morphology and significantly suppress the growth and proliferation of the breast cancer cell lines, MDA-MB-231 (ER-/PR-/HER2-, Basal-like) and BT474 (ER+/PR+/HER2+, Luminal B). The following genome-wide transcriptomic analysis of these cells suggested that FRY inter-acted with protein kinases relevant signaling pathways and induced massive changes in gene expression, including the activation of the Hippo/Yap pathway. Together, our data suggest that the FRY is required for mammary glands developments during pregnant periods, and affects breast cancer cell growth and proliferation.